PSYCHOLOGICAL EFFECTS OF COLORS AND COLOR THERAPY: रंगों का मनोवैज्ञानिक प्रभाव व रंग चिकित्सा - Rajouri, Pradeep (International Journal of Research -GRANTHAALAYAH, 2014)
Color is psychologically deeply associated with the path of our life or in other words, it is a true companionship of our life. An association without which life seems to be incomplete. It has an extremely diverse effect on our brain. This effect is sometimes positive and sometimes negative. Therefore, we should be alert and alert to the selection of colors and its connection. In order for color to have a good effect on our brain, we have to develop and mature our understanding and sensitivity towards colors. We have to know for sure that in which environment, using which colors can be used to make life prosperous and cheerful. Lack of psychological understanding of colors keeps us away from the development path of civilization. रंग मनोवैज्ञानिक ़रुप से हमारे जीवन के पथ के साथ गहराई से जुड़ा हुआ है या दुसरे शब्दों में कहें तो यह हमारे जीवन का एक सच्चा साहचर्य है। एक ऐसा साहचर्य जिसके बगैर जीवन अधूरा सा प्रतीत होता है। इसका हमारे मनोमस्तिष्क पर नित्य विविध प्रभाव पड़ता है। यह प्रभाव कभी-कभी साकारात्मक होता है तो कभी-कभी नाकारात्मक भी। इसलिए रंगों के चयन व इसके संसर्ग के प्रति हमें सचेत व सजग रहना चाहिए। रंग हमारे मनोमस्तिष्क पर अच्छा प्रभाव डाल सके इसके लिए हमें रंगों के प्रति अपनी समझ व संवेदनशीलता को विकसित व परिपक्व करना होगा। हमें यह निश्चित रुप से जानना होगा कि किन रंगों का प्रयोग किस वातावरण में करते हुए जीवन को समृ़द्ध व प्रफूल्लित बनाया जा सकता है। रंगों का मनोवैज्ञानिक समझ न होना हमें सभ्यता के विकास पथ से विमुख रखता है।